Antimicrobial polymers - Ocio, María José (Wiley, 2012)
"S book focuses on the coupling of plastics and biocides, with particular concentration on natural biocides and the nanofabrication of biocides, and of their final properties and activity. Chapters address the key technologies employed to impart antimicrobial behavior to polymers, including chemical modification of the polymers themselves, as well as discussing applications in food packaging, medical devices, nanomaterials, and coatings. The coverage balances outlining the technologies with explaining the mechanisms of antimicrobial behavior. Concluding chapters cover regulatory matters and human safety and environmental risks of antimicrobial polymers."--Resumé vydavatele
Keywords: polymery; plasty; antimikrobiální látky; chemické přísady; polymers; plastics; anti-microbial agents; chemical additives; kolektivní monografie; elektronické knihy; collective monographs; electronic books